PROFESIONALISME DAN KREDIBILITAS ASESOR DALAM PENINGKATAN MUTU PENDIDIKAN - Reresi, Marsianus (LOGOS: JURNAL PENDIDIKAN KEAGAMAAN KATOLIK, 2019)
This article is meant to explore issue of how is the performance of the School and Madrasah Assessors in carrying out their duties and functions for improving the quality of education? The results of the study emphasize that the assessors' professionalism and credibility have an effect on improving the quality of education. Professionalism of the Assessors indicates the aspects of knowledge, skills and attitudes. Whereas the Credibility of the Assessor emphasizes that the Assessor carries out his duties objectively based on guidelines or norms, so that the school / madrasah obtains the actual level of eligibility.